Mucoadhesive Multiparticulate Drug Delivery Systems: An Extensive Review of Patents - Someshwar Komati; Suryakanta Swain; Muddana Eswara Bhanoji Rao; Bikash Ranjan Jena; Vishali Dasi (Tabriz University of Medical Sciences, 2019)
Innovations in pharmaceutical research are striving for designing newer drug therapies to eradicate deadly diseases. Strategies for such inventions always flourish with keys and objectives of minimal adverse effects and effective treatment. Recent trends in pharmaceutical technology specify that mucoadhesive drug delivery system is particularly appropriate than oral control release, for getting local systematic delivery of drugs in GIT for an extended interval of time at a predetermined rate. However, it is somehow expensive and unpleasant sensation for some patients, but still it is needful for getting short enzymatic activity, simple administration without pain and evasion of fast pass metabolism. Usually the vehicles employed in drug delivery of mucoadhesive system have a significant impact that draws further attention to potential benefits like improved bioavailability of therapeutic agents, extensive drug residence time at the site of administration and a comparatively faster drug uptake into the systemic circulation. The drug release from mucoadhesive multiparticulates is contingent on several types of factors comprising carrier need to produce the multiparticles and quantity of medication drug contained in them. Mucoadhesion is characterized by selected theories and mechanisms. Various strategies emergent in mucoadhesive multiparticulate drug delivery system (MMDDS) by in-vitro as well as ex-vivo description and characterization are also critically discussed. Apart from these, the primary focus during this review is to highlight current patents, clinical status, and regulatory policy for enhancement of mucoadhesive multi-particulate drug delivery system in the present scenario